(3cja JJZdH Ydi GdVZhW GdfaSjI aj GdYed (B:s (3Odjd Yedj ddJNdU ef VZhW GdMjGI GdedMI (B/s - (3GdMOGO, YeGOs ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2006)
(3GdhUhd Gdi feW JacjQ jSGYO aj GdJZdH Ydi GdVZhW GdfaSjI(B- (3GdJZdH Ydi GdZVH(B- (3GdJNaja ef eTGYQ Gdbdb(B- (3GdJNaja ef MOI GdVZhW GdfaSjI GdfGJLI Yf GdYdGbGJ GdTNUjI(B- (3Gdbje hGdCgOGa hYdGbJgeG HGdVZhW GdfaSjI(B.s
Keywords: (3GdVZhW GdfaSjIs; (3GdYeds